Five go off in a caravan - Blyton, Enid (Hodder Children's London, 2001)
A caravan holiday for the Famous Five is bound to be an adventure! And when they stumble across a circus troupe, the gang are thrilled. But some of the circus people have more sinister plans than just clowning around